Tensile mechanical properties and failure mechanism of bamboo scrimber under different strain rates. (13th September 2021) - Wang, M.T.; Cai, X.F.; Lu, Y.B.; Noori, A.; Chen, F.M.; Chen, L.B.; Jiang, X.Q.; Liu, J.Q.
Highlights: Tensile behavior of bamboo scrimber is investigated. High-strain rate tests are performed by using SHTB. Original dynamic increase factor using the fitted parameters is provided. The properties of bamboo scrimber in two loading directions are compared. Failure mechanisms are observed by using SEM. Abstract: Bamboo Scrimber (BS) is a composite material with excellent mechanical properties fabricated by utilizing bamboo. This paper aimed to present the tensile properties and failure mechanism of BS under quasi-static and impact loading by quasi-static and split Hopkinson tensile tests. The Scanning Electron Microscope (SEM) photograph analysis was employed to investigate the failure process and modes of BS in both directions (longitudinal and transverse). Results show that the tensile properties of longitudinal specimens are much better than that of transverse. The strain rate effect increases tensile strength and ultimate strain as increasing strain rate from 10 −5 to about 1300 s −1 . The empirical formulas of dynamic increase factor were derived at various strain rates, and the turning strain rate is 689 and 525 s −1 for longitudinal and transverse specimens, respectively. The strength-to-weight ratio of BS is 83.54 kN.m/kg, higher than that of concrete and steel but lower than some timbers. Fiber fracture, matrix fracture, and interfacial debonding in the microscopic scale are reasons for the failure. Research on the impact tensile properties and failure mechanism of BS are helpful to its wide application for structure materials.